PENGEMBANGAN MEDIA SMART PUZZLE SUKU KATA UNTUK MELATIH KEMAMPUAN MEMBACA PESERTA DIDIK KELAS 1 SD NEGERI JEKETRO TEMANGGUNG - Anggun, Mei Sekar Anggun; Ida Zulaeha; Panca Dewi Purwati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to develop media that has been tested in terms of media experts and material experts to train students' reading skills. The type of research used is R & D (Research and Development) with the ADDIE model. Data collection methods use questionnaires, documentation and tests. The types of data used are qualitative data and quantitative data. The research subjects were grade 1 students at SD Negeri Jeketro. The general research results show that the score from the media validator obtained a percentage of 85% in the very appropriate category, the material validator score obtained a percentage of 84% in the very appropriate category and the student response score obtained a percentage of 88% in the very good category. And the change in the average score of all students from an average of 65 to 86 means that this smart syllable smart puzzle media can be used to train students' reading skills.